2013
DOI: 10.1111/jph.12085
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization of Fusarium Isolated From Maize in Syria

Abstract: Maize is the third most important cereal after wheat and barley in Syria. Maize plants are attacked by several Fusarium species causing mainly stalk and ear rot of maize which poses a major impact worldwide. Identification of Fusarium species is important for disease control and for assessment of exposure risk to mycotoxines. To identify Fusarium species attacking maize in Syria, a total of 32 Fusarium isolates were recovered from maize ears collected from four different geographical regions, mainly from Ghout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 35 publications
4
21
0
2
Order By: Relevance
“…This is in agreement with previous studies in eastern China (Qiu et al, 2015;Zhang et al, 2013b). F. verticillioides is also the most commonly isolated fungus from maize across the world (Aguin et al, 2014;Madania et al, 2013;Torres et al, 2001), while also F. proliferatum and F. subglutinans are commonly associated with FER. We observed a similar trend in China, where the ratio of F. subglutinans to F. proliferatum proved highest in Heilongjiang and Jilin in the most northern and coldest region in China, while in the more southern provinces Gansu and Hebei, no F. subglutinans was isolated.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in agreement with previous studies in eastern China (Qiu et al, 2015;Zhang et al, 2013b). F. verticillioides is also the most commonly isolated fungus from maize across the world (Aguin et al, 2014;Madania et al, 2013;Torres et al, 2001), while also F. proliferatum and F. subglutinans are commonly associated with FER. We observed a similar trend in China, where the ratio of F. subglutinans to F. proliferatum proved highest in Heilongjiang and Jilin in the most northern and coldest region in China, while in the more southern provinces Gansu and Hebei, no F. subglutinans was isolated.…”
Section: Discussionsupporting
confidence: 81%
“…Many FFSC species can produce fumonisins, a family of mycotoxins, causing various diseases in animals, and it has been associated epidemiologically with oesophageal cancer as well as neural tube defects in some human populations (Gelderblom et al, 1988;Marasas et al, 2004). In maize, Fusarium verticillioides, Fusarium proliferatum and Fusarium subglutinans are the most prevalent species worldwide (Adejumo et al, 2007;Aguin et al, 2014;Madania et al, 2013;Qiu et al, 2015;Torres et al, 2001). The first two species are potential fumonisin producers (Logrieco et al, 2002), while F. subglutinans is generally believed to be a fumonisin non-producer as the fumonisin biosynthetic genes are absent (Proctor et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the prompt detection and correct identification of Fusarium species in corn grains is important to monitor and prevent ear rot disease and the input of mycotoxins in the food chain (Jackson and Jablonski, 2004). The morphological identification of Fusarium species may not be sufficient for reliable identification of species (Madania et al, 2013;Rahjoo et al, 2008). DNA sequence-based molecular tools are increasingly used to enable accurate Fusarium species determination (Balajee et al, 2009;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Among the Fusarium species complex (teleomorph Gibberella fujikuroi), which comprises more than 50 species, Fusarium verticillioides, Fusarium proliferatum and Fusarium subglutinans are the main species that infect corn kernels (Krska et al, 1997;Leslie et al, 2006). F. verticillioides is the most common fumonisinproducing Fusarium species infecting corn kernels (Madania et al, 2013;Rahjoo et al, 2008;Orsi et al, 2000;Munkvold and Desjardins, 1997). Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number studies on the mode of attack by Fusarium on ungerminated seeds. Numerous investigations have been conducted with Fusarium species that infect maize seed (Fandohan et al, 2003;Duncan et al, 2010;Madania et al, 2013). In a more specialized study regarding the mode of seed infection by Fusarium species, Sauerborn et al (1996) showed the manner of pathogen penetration in the seed.…”
Section: The Pathogenicity Testmentioning
confidence: 99%